2017
DOI: 10.1186/s40249-017-0316-0
|View full text |Cite
|
Sign up to set email alerts
|

Habitat productivity and pyrethroid susceptibility status of Aedes aegypti mosquitoes in Dar es Salaam, Tanzania

Abstract: Background: Aedes aegypti (Diptera: Culicidae) is the main vector of the dengue virus globally. Dengue vector control is mainly based on reducing the vector population through interventions, which target potential breeding sites. However, in Tanzania, little is known about this vector's habitat productivity and insecticide susceptibility status to support evidence-based implementation of control measures. The present study aimed at assessing the productivity and susceptibility status of A. aegypti mosquitoes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 35 publications
6
25
0
Order By: Relevance
“…Since this study was the first of its kind in this geographical area, there were no immediate comparisons for the resistance profiles. However, in studies carried out in Dar es Salaam, Peru and Burkina Faso, resistance to pyrethroids and organophosphate was obvious [20,50,51]. Reduced susceptibility to pyrethroids observed in some of assays, and the resistance seen against bendiocarb in the rainy season are however signs that we must remain vigilant as insecticide resistance could rapidly spread among the vector populations once active control programmes begin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since this study was the first of its kind in this geographical area, there were no immediate comparisons for the resistance profiles. However, in studies carried out in Dar es Salaam, Peru and Burkina Faso, resistance to pyrethroids and organophosphate was obvious [20,50,51]. Reduced susceptibility to pyrethroids observed in some of assays, and the resistance seen against bendiocarb in the rainy season are however signs that we must remain vigilant as insecticide resistance could rapidly spread among the vector populations once active control programmes begin.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to earlier research, this study has shown that Ae. aegypti prefers breeding in clean and stagnant waters [19,20,41]. Common habitats for Ae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in coastal Tanzania, used tires and disposed containers were identified as commonest aquatic habitats for Ae. aegypti [11,20]. However, less is known regarding the ecology of these vectors in inland Tanzania, including small towns and rural settings.…”
Section: Introductionmentioning
confidence: 99%